1992
DOI: 10.3109/00365549209061333
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex Virus – The Most Frequently Isolated Pathogen in the Lungs of Patients with Severe Respiratory Distress

Abstract: 308 consecutive patients with severe or complicated respiratory tract infections underwent fiber-optic bronchoscopy in the search for a microbiological etiology. Protected brush specimens were used for bacterial cultures and bronchoalveolar lavage (BAL) for virus isolation and cytological examination. Herpes simplex virus (HSV) was the most commonly found pathogen and was isolated in 37 patients. 20 (54%) of them also had serological and/or cytological signs of HSV infection. 132 patients required assisted ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 18 publications
3
63
0
2
Order By: Relevance
“…Far less commonly HSV1 is found in the lower respiratory tract, although this lower incidence may in part be due to insufficient awareness of HSVP. Prellner et al showed that HSV1 is a far more common pathogen causing pneumonia than suspected [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Far less commonly HSV1 is found in the lower respiratory tract, although this lower incidence may in part be due to insufficient awareness of HSVP. Prellner et al showed that HSV1 is a far more common pathogen causing pneumonia than suspected [11].…”
Section: Discussionmentioning
confidence: 99%
“…Key words Herpes simplex virusṔ neumonia´Chest radiographÁ RDS state in patients who had had chemotherapy, organ transplantation, or other major surgery, and also in patients infected with human immunodeficiency virus (HIV) or other diseases which decrease immunity [7,8,9,10,11,12]. All these conditions were shown to be associated with an increased risk of herpes simplex virus pneumonia (HSVP).…”
mentioning
confidence: 99%
“…However, severe disease can develop in immunosuppressed patients: herpetic tracheobronchitis and pneumonia have been described in patients severely immunosuppressed due to burns, malignancies, chemotherapy, transplantation, AIDS, and cell-mediated immunity deficiencies [1,2]. Furthermore, HSV1 has been found (12 %) in the lungs of patients presenting with severe respiratory distress [3][4][5].In this report, we describe a patient with Crohn's disease who developed the acute respiratory distress syndrome (ARDS) due to pneumonia caused by HSV1. …”
mentioning
confidence: 99%
“…HSV-1 has previously been found in BAL fluid from immunocompromised patients (40% were AIDS patients) and in BAL fluid from patients with complicated respiratory tract infections [21,22]. The role of HSV-1 recovery in BAL fluid is still unclear, as it is not possible to distinguish between active disease and asymptomatic shedding of the virus.…”
Section: Discussionmentioning
confidence: 99%